CONSTITUTIONAL ADMINISTRATIVE CONSTITUTIONALISM: PERBANDINGAN KARAKTERISTIK KEKUASAAN LEGISLASI PRESIDEN DI INDONESIA DENGAN AMERIKA SERIKAT - Hadyan Iman Prasetya (Faculty of Law, Parahyangan Catholic University, 2024)
Recent studies conducted by American legal historians show that constitutional interpretation in the United States (U.S.) often arises from administrative agencies, a phenomenon called administrative constitutionalism. This supports the executive branch’s constitutional interpretation power, independent from the court. Similarly, Indonesia’s Constitution grants the President legislative power. By comparing this with U.S. administrative constitutionalism, this article, written descriptively through normative approach, examines the Indonesian President’s legislative power, termed constitutional administrative constitutionalism. The findings highlight three characteristics: (1) the U.S. dichotomy between president and administration does not apply in Indonesia, (2) Indonesia’s checks and balances occur during the debates in legislation drafting phase, unlike the post-enactment review in the U.S., and (3) Indonesia’s system operates under judicial supremacy, unlike the contesting judicial supremacy-departmentalism-popular constitutionalism in the U.S.